Mental Health Status among Adolescents of High Schools: A Cross-sectional Study - Dass, Baishali; Kandangwa, Binita; Pokharel, Rita (Journal of BP Koirala Institute of Health Sciences, 2021)
Background: Adolescents are prone to develop various psychosocial problems with a long-standing impact. We aimed to investigate the mental health status among adolescents from high schools in Dharan sub-metropolitan city.Methods: In this descriptive cross-sectional study, we enrolled 150 adolescents from two different schools of Dharan, using a stratified random sampling technique. The Pediatric Symptoms Checklist for Youth was used to assess their mental health status. A score of 30 or more was considered as a mental health problem. Poverty, family dispute, punishment, and personal and family history of a psychiatric condition were considered as potential predictors of mental health problem. The chi-square test was applied to identify the predictors of mental health problem.Results: The final analysis included 141 samples. More than 60% of the students belonged to the age group 13-15 years, and 52.5% were females. About 59.6% were Janajatis, and 61% were Hindus. The majority (63.8%) were living below the poverty line. The majority (83.7%) had no dispute in the family. All the students had received punishment, and 51.1% had received it at home. One-third of the students had mental health problem. The presence of mental health problem was significantly associated with nuclear family status (p = 0.04), and history of a family dispute (p = 0.04).Conclusion: Mental health problem was common among adolescents, and it was associated with the nuclear family structure and the presence of family dispute.